2016
DOI: 10.1038/srep33240
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis reveals variants on chromosome 19 that contribute to childhood risk of chronic otitis media with effusion

Abstract: To identify genetic risk factors of childhood otitis media (OM), a genome-wide association study was performed on Finnish subjects, 829 affected children, and 2118 randomly selected controls. The most significant and validated finding was an association with an 80 kb region on chromosome 19. It includes the variants rs16974263 (P = 1.77 × 10−7, OR = 1.59), rs268662 (P = 1.564 × 10−6, OR = 1.54), and rs4150992 (P = 3.37 × 10−6, OR = 1.52), and harbors the genes PLD3, SERTAD1, SERTAD3, HIPK4, PRX, and BLVRB, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…The Finnish families (Einarsdottir et al, ; Hafrén et al, ) were ascertained from the Helsinki University Hospital upon referral of the proband for otitis media. Finnish patients were considered positive for otitis media if they had an insertion of tympanostomy tubes, effusive otitis media for >2 months, or recurrent otitis media (i.e., >3 episodes in 6 months or >4 episodes in 12 months).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Finnish families (Einarsdottir et al, ; Hafrén et al, ) were ascertained from the Helsinki University Hospital upon referral of the proband for otitis media. Finnish patients were considered positive for otitis media if they had an insertion of tympanostomy tubes, effusive otitis media for >2 months, or recurrent otitis media (i.e., >3 episodes in 6 months or >4 episodes in 12 months).…”
Section: Methodsmentioning
confidence: 99%
“…The identification of genetic risk factors and disease‐related pathways is one area of otitis media study for which efficient tools are available but discovery remains very limited compared with other common complex, inflammatory, immune, or infectious disorders. Although the most current catalog of genome‐wide association studies (GWAS) lists > 3,500 studies, only five studies (<0.15%) using common single nucleotide polymorphisms (SNP) identified significant loci for otitis media susceptibility, namely: intergenic rs10497394 on 2q31.1 (Allen et al, ); rs16974263 in the 19q13.2 region which is intronic to PRX (MIM 605725) encoding periaxin (Einarsdottir et al, ); FNDC1 (MIM 609991) at 6q25.3 (van Ingen et al, ); and rs76488276 at 16p12.3 that is approximately 94 kb away from innate immune gene GP2 (MIM 602977; Li et al, ). In the largest GWAS to date including >120,000 European‐descent individuals (Pickrell et al, ; Tian et al, ), 15 risk variants were identified, including four SNPs that were coding and/or intronic but in linkage disequilibrium with coding variants.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the GWAS of the Minnesota and Pittsburg cohorts identified a SNP (rs10497394 on chromosome 2) that showed a significant association (GWAS discovery P = 1.30 × 10 −5 , independent otitis media population P meta = 1.52 × 10 −8 ) with susceptibility to either chronic OME or recurrent AOM (Allen et al, 2013). Finally, in a Finnish cohort (829 affected children and 2,118 randomly selected controls), the variants rs16974263 (GWAS discovery P = 1.77 × 10 −7 , sub-phenotype analysis P meta = 2.92 × 10 −8 ), rs268662 (P = 1.564 × 10 −6 ), and rs4150992 (P = 3.37 × 10 −6 ) were the most significant variants associated with COME (Einarsdottir et al, 2016). In van Ingen et al (2016) performed GWAS on a cohort of AOM children of European descent and reported a statistically significant association at 6q25.3 locus (rs2932989, P meta = 2.15 × 10 −9 ).…”
Section: Genome-wide Association Studiesmentioning
confidence: 97%
“…One of the potential uses of our in vitro model is that is may be useful for the study of genes associated with OM. Multiple genetic association studies have been undertaken to identify human genes associated with OM [22][23][24]. Additionally, loss of function of multiple genes have been shown to lead to the development of OM-like phenotypes in mice [25,26].…”
Section: Expression Of Om Associated Genes In the In Vitro Mouse Middmentioning
confidence: 99%